2018
DOI: 10.3892/ol.2018.9194
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA‑CCAT2 promotes the occurrence of non‑small cell lung cancer by regulating the Wnt/β‑catenin signaling pathway

Abstract: The present study aimed to investigate the biological function of colon cancer-associated transcript 2 (CCAT2) in the occurrence and progression of non-small cell lung carcinoma (NSCLC) and its potential use in the early diagnosis and molecular-targeted therapy of NSCLC. The tumor tissues, para-carcinoma tissues and associated clinical data of 36 patients with NSCLC were collected in order to detect the expression of CCAT2 and assess the impact of factors including histopathological type, Tumor-Node-Metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The role of lncRNAs in various biological processes, such as cell differentiation, proliferation and apoptosis in various diseases, including cancer, has received increasing attention (10)(11)(12). The colon cancer associated transcript 2 (CCAT2) gene has been reported to be upregulated in various types of human cancer, including gastric cancer, non-small cell lung cancer, esophageal cancer (13)(14)(15)(16)(17), hepatocellular carcinoma (18,19) and other tumors (20)(21)(22), and it is associated with the occurrence and metastasis of cancer, as well as poor prognosis. Previous studies have demonstrated that lncRNA CCAT2 is localized in the 8q24 genomic region, which has been identified as the first reproducible genetic risk site (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of lncRNAs in various biological processes, such as cell differentiation, proliferation and apoptosis in various diseases, including cancer, has received increasing attention (10)(11)(12). The colon cancer associated transcript 2 (CCAT2) gene has been reported to be upregulated in various types of human cancer, including gastric cancer, non-small cell lung cancer, esophageal cancer (13)(14)(15)(16)(17), hepatocellular carcinoma (18,19) and other tumors (20)(21)(22), and it is associated with the occurrence and metastasis of cancer, as well as poor prognosis. Previous studies have demonstrated that lncRNA CCAT2 is localized in the 8q24 genomic region, which has been identified as the first reproducible genetic risk site (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that by activating the Wnt/β-catenin signaling pathway, lncRNA CCAT2 affects oral squamous cell carcinoma, ovarian cancer and renal cell carcinoma (33), as well as non-small cell lung cancer, breast cancer, esophageal cancer and glioma (15,17,(33)(34)(35)(36)(37). However, to the best of our knowledge, no studies have previously examined the relationship between CCAT2 and the Wnt/β-catenin signaling pathway in PCa, and its potential regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA_102171 silencing suppresses the proliferation, migration and invasion of PTC cells and promotes apoptosis via regulating the Wnt/β-catenin pathway ( 35 ). The association between different lncRNAs and the Wnt/β-catenin signaling pathway in cancer cells is widely acknowledged ( 21 , 22 , 36 , 37 ). Zhao et al ( 21 ) found that CCAT2 could facilitate the occurrence of non-small lung cancer through activating the Wnt/β-catenin cascade.…”
Section: Discussionmentioning
confidence: 99%
“…The association between different lncRNAs and the Wnt/β-catenin signaling pathway in cancer cells is widely acknowledged ( 21 , 22 , 36 , 37 ). Zhao et al ( 21 ) found that CCAT2 could facilitate the occurrence of non-small lung cancer through activating the Wnt/β-catenin cascade. Ma et al ( 22 ) revealed that knocking down CCAT2 suppresses the malignancy of oral squamous cell carcinoma through inhibiting the Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CCAT2 promoted the occurrence of NSCLC by regulating the Wnt/β-catenin signaling pathway. [35] Zhang et al found that CCAT2 was upregulated in ESCC tissues, especially in cases with lymph node metastasis (LNM), advanced TNM stages, and MYC amplification. Furthermore, the level of CCAT2 was positively correlated with TNM stages, LNM, and the number of positive lymph nodes, indicating CCAT2 might be a prognostic biomarker and therapeutic target for ESCC.…”
Section: Discussionmentioning
confidence: 99%